Subsidizing Inequality? Rethinking Housing Affordability in the Age of Market-Driven Urbanism - Aqmala Fatma Kurniasih; Joko Adianto (International Journal of Built Environment and Scientific Research, 2026)
The global housing affordability crisis is caused by the commodification of land and housing due to market capitalism pressures. Although government intervention through land and housing subsidies has been widely implemented, the effectiveness of these policies in addressing spatial inequality and improving access for low-income communities remains debatable. This study aims to explore how effective land and housing subsidies function as government policies in reducing housing inequality amid market dominance. This study conducted a systematic literature review (SLR) using the PRISMA protocol to identify and analyze 384 articles published between 1980 and 2025. After a rigorous selection process, 13 peer-reviewed articles were selected for in-depth analysis. The main findings indicate that land subsidies, although designed to improve affordability, often exacerbate social and spatial segregation, particularly in developing countries such as China and South Africa. Conversely, in developed countries such as America, the United Kingdom and Australia, planning policies such as inclusive zoning, which are often implemented, still fail to include the most marginalized groups without sustained fiscal intervention. The results of this study highlight the importance of designing more adaptive and context-sensitive subsidy policies, particularly for developing countries like Indonesia. These findings provide a foundation for formulating more inclusive policies that prioritize spatial justice in affordable housing development.